Use of Sociology Concepts as the Basis of a Model for Improving Accessibility in Smart Cities - Santos, Vítor (2018)
Santos, V., Santos, C., & Cardoso, T. (2015). Use of Sociology Concepts as the Basis of a Model for Improving Accessibility in Smart Cities. In C. Velasco, G. Weber, J. Barroso, Y. Mohamad, & H. Paredes (Eds.), Proceedings of the 6th International Conference on Software Development and Technologies for Enhancing Accessibility and Fighting Info-exclusion (Vol. 67, pp. 409-418). (Procedia Computer Science). Elsevier. https://doi.org/10.1016/j.procs.2015.09.286